Histone deacetylase signaling in cardioprotection - Lehmann, Lorenz; Jones, Barbara Christine; Stanmore, David; Backs, Johannes (Cellular and molecular life sciences, 2014)
Cardiovascular disease (CVD) represents a major challenge for health care systems, both in terms of the high mortality associated with it and the huge economic burden of its treatment. Although CVD represents a diverse range of disorders, they share common compensatory changes in the heart at the structural, cellular, and molecular level that, in the long term, can become maladaptive and lead to heart failure. Treatment of adverse cardiac remodeling is therefore an important step in preventing this fatal progression. Although previous efforts have been primarily focused on inhibition of deleterious signaling cascades, the stimulation of endogenous cardioprotective mechanisms offers a potent therapeutic tool. In this review, we discuss class I and class II histone deacetylases, a subset of chromatin-modifying enzymes known to have critical roles in the regulation of cardiac remodeling. In particular, we discuss their molecular modes of action and go on to consider how their inhibition or the stimulation of their intrinsic cardioprotective properties may provide a potential therapeutic route for the clinical treatment of CVD.
Published online: 06 December 2013
Gesehen am 08.12.2021